Pengaruh Budaya Organisasi, Fleksibilitas Kerja Dan Kompetensi Terhadap Kepuasan Kerja Pegawai Pada Rumah Sakit Umum Daerah Sidikalang - Rawaty Purba; Henri Saragih; Mangasa Panjaitan (CV. Ulil Albab Corp, 2026)
The purpose of this study is to determine the effect of organizational culture, work flexibility, and competence on job satisfaction at the Sidikalang Regional General Hospital. The population in this study consisted of all hospital employees, totaling 371 employees. The sampling technique used was probability sampling with the Slovin formula, resulting in a sample of 78 employees. The data analysis techniques employed were statistical tests including regression analysis, t-test, Moderated Regression Analysis (MRA), and the coefficient of determination (R-Square). The results of this study indicate that organizational culture has a partial and significant effect on employee job satisfaction at Sidikalang Regional General Hospital. Work flexibility also has a partial and significant effect on employee job satisfaction at Sidikalang Regional General Hospital. Competence has a partial and significant effect on employee job satisfaction at Sidikalang Regional General Hospital. Based on the analysis of the coefficient of determination, the adjusted R-Square value obtained was 0.391 or 39%, which means that organizational culture, work flexibility, and competence influence employee job satisfaction by 39%, while the remaining 100%-39%=61% is influenced by other variables or factors not examined in this study.